Turning DIN 19682-7 Procedure of Infiltration Rate of Soils Test into the Mobile App for Cloud Storage - Sulistyo, Totok; Kiptiah, Mariatul; Kusumayudha, Sari Bahagiarti; Cahyadi, Tedy Agung; Fajar, Reza Adhi (ComTech: Computer, Mathematics and Engineering Applications, 2025)
The in-situ soil infiltration test using A Double Ring Infiltrometer (DRI) apparatus can be conducted in the field according to DIN 19682-7 standards and procedures. As required by these standards, the traditional paper-based measurement form can be replaced with a new application developed to meet standard requirements. The DRI apparatus consists of two concentric rings placed in the soil, filled with water, while the outer ring maintains a constant water level. The water level drop in the inner ring is observed and recorded at regular intervals. The infiltration rate can be calculated for each interval by measuring the change in water height over time. This new application facilitates the automatic calculation of both the actual soil infiltration rate and the Horton soil infiltration model. Comparison tests between the application results and Excel calculations have yielded similar outcomes. The goal of this research is to develop a mobile web-based application for recording data and calculating soil infiltration measurements using the DRI method. The research methodology involves transforming the measurement procedure into a concept, designing the application, and then implementing that design. By replacing the paper-based process, this application will enhance the efficiency, accuracy, and flexibility of soil infiltration measurement projects in various locations. Furthermore, the data will be stored in the cloud, allowing for crowdsourced infiltration data collection and monitoring from any location, including the office.